Consumer behavior in a fitness gym and Health Club: study of frequency, satisfaction and retention - Meireles, Pedro (2017)
This study aims to understand the relationship between the frequency of use, satisfaction, and retention of members in fitness, in a Health Club located in Oporto. In the fitness market it is indispensable to understand the characteristics of faithful members, in order to act appropriately with each segment. Accordingly, the frequency which a member goes to the gym (Ferrand, Robinson & Valette, 2010), their satisfaction (Gonçalves, 2012) and retention of members in fitness - if the members remain subscribed for a long time and influence other people to become members (Alexandris, Zahariadis, Tsorbatzoudis & Grouios, 2004) - are key variables to understand them. Data was collected in 2014, with a sample of 146 members of the studied fitness club. The instrument was constituted by the sample characterization and another part containing questions to understand the behavior of fitness consumers: frequency of use, satisfaction and retention. Subsequently it was conducted a pretest with 30 members and based on these results the final version of the instrument was prepared. The statistical analysis was performed with SPSS software: descriptive and comparative analyses were performed. Cronbach's alpha was used to assess the internal consistency of the satisfaction and retention items. In this study the percentage of those going three or more times to the gym is significant (64%; n=96). These results are consistent with satisfaction in the gym since most members are very satisfied with their gym, intend to remain (92.5%; n=138) and would recommend the gym to others (84.2%; n=123). The results indicate that the health club managers must act to keep those who are less likely to remain, those with less frequent use, and have a lower satisfaction and consequently lower retention.